Due libri: un legame storico - Vari, Autori (Il sogno della farfalla, 2013)
We are publishing the two papers presented at the book launches of two books, which appeared for the first time in Italy between 1979 and 1980 and have recently been republished: The story of Anna O., by Lucy Freeman, and Bambino donna e trasformazione dell’uomo by Massimo Fagioli. The former recounts the story of Bertha Pappenheim, the patient described by J. Breuer and S. Freud in Studies on Hysteria, revealing the failure of this therapy; in the latter Fagioli, recounting his personal and scientific development over the years, offers a critique and a way out of this failure. The papers focus on the growth of psychotherapy from its origins at the end of the 18th century until today, and on the story of the Collective Analysis and the particular relationship which has developed between the psychiatrist Fagioli and its participants.